Hotness revisited - Copeland, Lyndsey Hoh (International Library of African Music, 2022)
This article revisits a familiar trope in African music studies: “hot rhythm.” By tracing the lineage of the “hot” concept through twentieth and twenty-first century Africanist scholarship, I demonstrate the prevalence of foreign-made metaphors in contemporary African music studies and suggest scholars rethink whose metaphor and whose hotness they employ. What is the relationship of the metaphorically hot to phenomenal sensations of hotness? And what is the relationship of the “hot” concept to lived experiences of heat? I explore the relevance of heat as a material condition and hotness as a condition of being to music making in Africa with reference to ethnographic research with amateur brass band musicians in the Republic of Benin. This essay’s primary contribution is to apply an ecomusicological critique to an enduring climatic metaphor in African music discourse. My appeal to rethink the long-accepted analytical metaphor of “hot rhythm” further strives to destabilise entrenched theories of African music formulated by foreign scholars and instead focus attention on African concepts and experiences.
Keywords: Metaphor; Brass bands; Ecomusicology; West Africa; Discourse analysis; Benin; Hot Rhythm; Climatic Metaphor; African Music